Strengthening the Human Resource Capacity of MSME Actors in Bojongsari Village through Managerial Skills Training and Business Digitalization - Sunarsi, Denok; Sudaryana, Yayan; Supratikta, Hadi; Fernando, Louis; Firmansyah, Tantan (Pasundan Community Service Development, 2025)
This community service aims to strengthen the capacity of human resources of micro, small, and medium enterprise (MSME) actors in Bojongsari Village through training in managerial skills and business digitalization. MSME actors in this area often face various challenges, both in terms of limited managerial capabilities, such as financial management and business planning, as well as in terms of technology, particularly related to marketing and digital business management. This activity was carried out using a combination of lectures, hands-on practice, and discussions involving 30 local MSME actors. The topics covered include the basics of business management, such as business planning, financial management, and digital marketing strategies through social media platforms and e-commerce. The results of this activity showed an improvement in participants' managerial skills, reflected in their ability to create more structured business plans and manage their business finances more effectively. Additionally, the application of business digitalization has started to take shape, with participants now having social media accounts and utilizing online platforms to market their products. However, challenges still exist, especially in terms of limited access to technology and a lack of understanding in digital data analysis. Therefore, further training is necessary to ensure that MSME actors can maximize the use of technology. With this training, it is hoped that MSMEs in Bojongsari Village can develop more competitively in the increasingly digital market.